Hilary Hahn an intimate portrait (Night and Nightfrog, 2005)
Music experts have called Hilary Hann a "talent of the century," and there is no doubt that she is one of the next in the metropolises of the world with the professionalism and self-possession of a pop star. Anyone wishing to make a portrait of Hilary Hahn only do so on the go. We accompany the artist on her travels, which include stops at the Hong Kong Cultural Center, the Berlin Philharmonie and the famous Abbey Road Studios in London. An intimate portrait emerges, of a cosmopolitan youn woman who is able to fill well known classical works with a new intensity that is also fascinating for young audiences. Musical Programme Edgar Meyer, Violin Concerto Erich Wolfgang Korngold, Concerto for Violin and Orchestra op.35 James Horner, The Village Wolfgang Amadeus Mozart, Sonata for Violin and Piano Johann Sebastian Bach, Partita No. 2 Ralph Vaughan Williams, The Lark Ascending Niccolo Paganini, Violin Concerto No. 1 Hilary Hahn, violin